Cross-Validation of The Australian-Developed Smoking Inventory: An Investigation of Motives Underlying The Decision-Making Processes Leading to The Uptake, Maintenance, and Possible Cessation of Smoking among Students in Assumption University - Sae-Jong, Hathairat; Ho, Robert (Scholar: Human Sciences, 2017)
The present study was designed to cross-validate the Australian developed Australian Smoking Inventory as applied to the Thai context. Exploratory factor analysis identified the three factors of ‘perceived utility of smoking’, ‘pleasure/addiction needs’, and ‘need for social acceptance’ as three major motives for smoking behavior among Thai young adults. These findings are similar to those obtained from Ho’s (1989) Australian study and suggest that Thais and Australian hold similar beliefs about the decision-making processes underlying smoking behaviors. The implications of the study’s findings, which include the development of intervention programs and strategies to lower the motivation and perception of the perceived utility of smoking, are discussed.